Nanopartículas de ródio suportadas em carvão ativado como catalisadores para reações de oxidação - Vieira, Tales Giuliano (2015)
In this work was prepared catalysts containing nanoparticle rhodium (Rh) supported on activated carbon and their potential tested in catalytic oxidation reactions. The characterization data for transmission electron microscopy for not calcined material (CA-Rh) and the catalyst subjected to heat treatment (CA-Rh-c) showed the presence of Rh nanoparticles with diameter of about 2.4 nm distributed by the support surface. Analyzes per X-ray diffraction and scanning electron microscopy also showed the presence of Rh at the nanoscale. The catalytic activity of the materials was evaluated by decomposition at alkaline pH with hydrogen peroxide in presence of methylene blue in aqueous medium, suggesting a mechanism the radical oxidation of organic species. Was also evaluated the reuse of the catalyst after several cycles, yielding about 30% of methylene blue decomposition reaction after the 10th cycle. The oxidation of Methylene Blue was followed by analysis by mass spectrometry with electrospray ionization, not being identified intermediate reactions, suggesting a mineralization of organic substances or a possible selective adsorption of oxidation products. The catalysts were also used in studies of oxidation of cyclohexene in the presence of hydrogen peroxide affording a 73.7% selectivity to the corresponding allylic alcohol and alkene conversion close to 58% . Was identified further oxidation products less abundant as the corresponding epoxide or vinyl alcohol. The abundances of the products identified are consistent with the proposed radical mechanism based on the stability of the formed carbonaceous radicals. Oxidation of limonene was also studied in the present work achieving a 47.20% conversion of the terpene in the presence of CA-Rh catalyst and hydrogen peroxide. Similarly, several oxidation products were identified, highlighting the substance linalool, with about 46% selectivity. In both cases the formed products were identified by gas chromatography and mass spectrometry.